Digital Transformation, Capital Structure, And Liquidity: Implications For Return On Assets (ROA) - Andriani, Nini; Utami, Ayu Putri; Farid, Erwan Sastrawan; Samudra, Suryadi; R, Abdul Azis (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to empirically analyze the implications of digital transformation, capital structure, and liquidity on corporate financial performance. Digitalization in this study is measured through the proportion of intangible assets in the form of software, capital structure is measured through Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), liquidity is represented by current ratio and quick ratio, while financial performance is represented by Return on Assets (ROA) ratio. The research method used is quantitative research with the help of SPSS 25 statistical software. The population is technology sector companies listed on the IDX with a total of 47 companies. The sample amounted to 17 companies, with the sampling method being purposive sampling. Data is taken from the company's financial statements for 2020-2024. The results showed that simultaneously, the variables   digital transformation, DAR, DER, current ratio, and quick ratio had a significant effect on ROA. Partially, digital transformation and quick ratio have a significant positive effect on ROA, while DAR, DER, and current ratio show a significant negative effect on ROA.